As peculiaridades processuais dos processos por acidentes de trabalho em Portugal - Silveiro de Barros, M. (I Seminário Hispano-Português de Direito da Segurança Social, na Faculdade de Direito da Universidade de A Coruña., 2018)
The procedural legal regime of accidents at work in Portugal presents several comparative singularities regarding the protection of such social risk. The first singularity is present in the procedural rules which regulate the repairing of accidents at work and, contrary to the general rule that states that the litigation on social security is an administrative litigation, those rules state that the procedural regulation of accidents at work will be decided by the Labor Courts of Law, under a special labor procedure, which is structured in two phases: conciliatory and judicial. On the other hand, unlike Spain, in Portugal, the passive procedural party is, as a rule, a private insurance company represented by an Attorney, and not the Social Security Institute. This is due to the fact that Portugal keeps a substantive regime of protection of accidents at work based on a insurance policy of accidents at work by which the employer transfers its objective civil liability to the insurance company. Also unlike Spain, the active procedural party in the litigation on accidents at work is not the beneficiary of Social Security, but an employee, or his family members, who shall be represented by the Public Prosecutor’s Office, or in case of contracting an Attorney to represent them, the Public Prosecutor will keep an accessory intervention.